Pengaruh Populasi dan Jenis Semai Mangrove Terhadap Laju Pertumbuhan Ikan Bandeng (Chanos chanos) dalam Tambak Wanamina - Budihastuti, Rini; Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Milkfish culture in silvofishery pond generally depend on environment services which is naturally provided by mangrove stands within. But, optimization of silvofishery structure for the growth of Milkfish is not well improved. This research aimed to know the growth rate of Milkfish in silvofishery pond occupying different stand population and species composition of mangrove and to analyze the difference of growth rate of Milkfish based on the applied treatments. Research was conducted for 4 months including treatments of L1V1 (5 stands of Avicennia marina); L1V2 (5 stands of Rhizophora mucronata); L1V3 (5 stands ofmixed species); L2V1 (10 stands ofA. marina); L2V2 (10 stands ofR. mucronata); L2V3 (10 stands of mixed species); L3V1 (15 stands ofA. marina); L3V2 (15 stands ofR. mucronata); dan L3V3 (15 stands of mixed species). Measurements on the growth of Milkfish were conducted through field sampling involving 30 samples of Milkfish for each treatment. Observed growth parameters including absolute daily length growth, absolute daily weight growth and specific growth rate (SGR). Data collections were conducted for 3 repetitions. Data analysis were conducted with t-test and ANOVA. The research resulted there were variation on the growth rate of Milkfish including absolute daily length growth, absolute daily weight growth and SGR based on growth period nor treatments. Analysis showed there were significant difference of absolute daily length growth and SGR between growth period, but not on the absolute daily weight growth. Growth period and stand population of mangrove simultaneously effect the absolute daily length growth and SGR of Milkfish. While species composition of mangrove species did not have significant effect to the growth of Milkfish. Â  Keywords: Milkfish, stands population, species composition, growth, silvofishery